Impact of dental care on the oral health of in patients with trauma sequelae (Research, Society and Development, 2021)
This study aims to assess oral health before and after dental care to adult patients restricted to bed with trauma sequelae, admitted to the Instituto Doutor José Frota (IJF) hospital, located in the city of Fortaleza, in the state of Ceará. This is a longitudinal study with adult patients with motor and cognitive disabilities, diagnosis of traumatic brain injury, spinal cord trauma, and exogenous intoxication. We evaluated 39 patients, using the World Health Organization (WHO) dental caries index and Bedside oral exam (BOE) before and after dental care. After two dental consultations, there was a reduction of 46% of decayed teeth, poor oral health decreased by 11% and 29.6% of the BOE index, and good oral health increased by 57%. Although dental care in bed is challenging, it has proved effective, improving the health of the oral mucosa, perioral and dental surfaces and, consequently, reducing the likelihood of changes in oral health.